The Relationship Between Employees’ Incentives And Performance At Ghana Oil Company Limited In The Southern Zone Of Ghana - Tetteh, Kwao Isaac; Fentim, Darkwa Bernard; Dorothy, Amfo-Antiri (Advances in Social Sciences Research Journal, 2015)
The purpose of this paper was to examine the relationship between employees’ incentives and performance at Ghana Oil Company limited in the southern zone, Ghana. One hundred and ninety five (195) employees of GOIL were selected for the study. The study used a mixture of descriptive and correlational survey design. Questionnaire was the main instrument used to collect the data for the study. The study revealed that various forms of incentive packages (financial and non-financial) have a positive relationship with employees’ satisfaction and job performance. The study also recommended that, the management of GOIL should develop, nurture and maintain attractive forms of incentive packages as motivational tool if they want to satisfied employees and also ensure a congenial work environment, recognise and reward hardworking staff since this will encourage and motivate employees to be satisfied in their job which will lead to a significant increase in their performance.